If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -3)(y + 2) = 0 Reorder the terms: (-3 + X)(y + 2) = 0 Reorder the terms: (-3 + X)(2 + y) = 0 Multiply (-3 + X) * (2 + y) (-3(2 + y) + X(2 + y)) = 0 ((2 * -3 + y * -3) + X(2 + y)) = 0 ((-6 + -3y) + X(2 + y)) = 0 (-6 + -3y + (2 * X + y * X)) = 0 (-6 + -3y + (2X + yX)) = 0 Reorder the terms: (-6 + 2X + -3y + yX) = 0 (-6 + 2X + -3y + yX) = 0 Solving -6 + 2X + -3y + yX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 2X + -3y + 6 + yX = 0 + 6 Reorder the terms: -6 + 6 + 2X + -3y + yX = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2X + -3y + yX = 0 + 6 2X + -3y + yX = 0 + 6 Combine like terms: 0 + 6 = 6 2X + -3y + yX = 6 Add '3y' to each side of the equation. 2X + -3y + 3y + yX = 6 + 3y Combine like terms: -3y + 3y = 0 2X + 0 + yX = 6 + 3y 2X + yX = 6 + 3y Reorder the terms: -6 + 2X + -3y + yX = 6 + 3y + -6 + -3y Reorder the terms: -6 + 2X + -3y + yX = 6 + -6 + 3y + -3y Combine like terms: 6 + -6 = 0 -6 + 2X + -3y + yX = 0 + 3y + -3y -6 + 2X + -3y + yX = 3y + -3y Combine like terms: 3y + -3y = 0 -6 + 2X + -3y + yX = 0 The solution to this equation could not be determined.
| 3x-32+4x-33=180 | | -3+.6x=4 | | -6(w+8)= | | 2h-18= | | 3x^2+45-13500=0 | | x^2+y^2-x+2y+1=0 | | 3z^3*z*4= | | y=8sinx | | 4x-29=3x-78 | | x^3+8x^2-26x-33=0 | | 9+2(y-6)=20 | | -6-11x=7x-12 | | 2x^2+56x-29=0 | | (4u+7)(6-u)=0 | | 7y=28y+6 | | 2z^2-17z+30= | | -9+5x=-14 | | -6=-3r | | (Y+5)+x=2.5y | | 70-3x=90-43x | | 3z^3*z= | | 9+3q=12+2q | | 11v-9v=4 | | 70-3x=90-11x | | (9x+12y)(9x-12y)= | | (Y-5)+x=2.5y | | 5(c-4)=6(c-5) | | log(x)-log(x+11)=-1 | | 3m-29=-44+8m | | 5(x+10)=7x-32 | | 4800000=2900000+1600x | | 3x^2+32x+20= |